Diagnostic center for primary care patients with nonspecific symptoms and suspected cancer: compliance to workflow and accuracy of tests and examinations - Emelie Stenman; Karolina Palmér; Stefan Rydén; Charlotta Sävblom; Jianguang Ji; Jan Sundquist (Taylor & Francis Group, 2021)
Objective To evaluate compliance to workflow and accuracy of tests in Sweden's first fast-track referral pathway for patients with nonspecific symptoms and suspected cancer (SCAN). Design Prospective cohort study with consecutive inclusion of patients referred to the diagnostic center (DC). Setting Patients with nonspecific symptoms were examined in primary care according to a protocol including two test packages and diagnostic imaging. If symptoms were not explained, patients were referred to the DC and a DC-test package was taken. At the DC, further investigations resulted in diagnosis/no diagnosis. Subjects A total of 290 patients, median age 69 years (interquartile range [IQR] 59-76), 48% men, participated. A total of 64 (22%) were diagnosed with cancer, 186 (64%) with non-malignant disease and 40 (14%) had no new disease. Main outcome measure Compliance was estimated by percentage of compulsory tests taken. Test accuracy was assessed by likelihood ratios (LRs) regarding cancer. Results A total of 23 (8%) patients had taken both primary care packages, whereas 150 (52%) patients went through entire diagnostic imaging. Abnormal pulmonary X-ray, peak expiratory flow (PEF) and calcium had the highest LRs in primary care (3.5; 3.2; 2.7). A total of 105 (36%) took the complete DC-package, of which bilirubin and cytomegalovirus had the highest LRs (11.5; 10.9). The median number (IQR) of abnormal primary care tests was 5 (3-6) for cancer, 3 (2-6) for other diagnoses and 1 (0-3) for no diagnosis. Conclusions Compliance to test packages in primary care was low, which warrants review of the workflow. Few single tests had high accuracy regarding cancer, but the number of abnormal tests can provide guidance in complicated investigations of suspected malignancies.KEY POINTS Fast-track referral pathways for patients with nonspecific serious symptoms have been implemented in several countries and are part of the national cancer strategy in all of Scandinavia. Compliance with compulsory tests in primary care was modest in this study; 8% of the patients had taken the entire compulsory test packages. Few single compulsory tests had high accuracy regarding subsequent cancer, which warrants a review of tests and examinations. However, patients diagnosed with cancer had a higher number of abnormal test results compared to the other groups.